Daya terima nugget ikan depik dengan substitusi tepung mocaf - Lestari, Wanda; Maisyarah, Maisyarah; Purba, Tuty Hertati; Angkat, Abdul Hairuddin (Journal of Pharmaceutical and Sciences, 2023)
Nuggets are processed meat product that can increase the use and storage values of the meat itself. Making nuggets from depik fish with the substitution of mocaf flour increases the selling values of the depik fish. The aim is to determine the acceptability and hedonic quality and nutritional content of the best formulas vor nugget products. Experimental research using a completely randomized design (CRD) approach to the formulation of the basic material for making nuggets with the addition of depik fish with mocaf flour substitution that is four treatments and two repilications to obtain 8 experimental units, the data were analyzed by One Way ANOVA with Duncan test. The results based on hedonic tests show that F3 (60% Mocaf Flour + 40% Wheat Flour) averaged 3,81 the best-selected formula. Whereas the hedonic quality test showed that F3 was the best formulation with a total value of 3.74 with a grayish-white color clarification, depik fish aroma, savory taste and chewy texture. Water content is 12.24%, ash content is 7.38% and protein content is 5.16%. Conclusion:  the best depik fish nuggets formula is F3 formula.